The seventh and eighth dogmas of empiricism and semantic view of scientific theories - León Untiveros, Miguel (2015)
In this paper we show there is a relationship between the dogmas of empiricism and the semanticview of empirical sciences. We analyze the special relationship between the so-called seventh andeighth dogmas of empiricism and semantic view of empirical sciences, and we claim there is noway to improve logical empiricism (in a liberal flavor) in order to overcome these dogmas.